Analisis Diskursus Ekonomi Kerakyatan dalam Perspektif Maqasid Syariah - Noviyanti, Ririn (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2019)
Economic democracy is an economy that basically use the concept of sovereignty of the people,with the aim of achieving social justice for all Indonesian peolpe. Economic democracy is a reaction and a correction of the practices of the colonial system and economic structure. The main pioneer of economic democracy is Mohmmad Hatta, dubbed as the father of Indonesia cooperation. Maqa??id shari?ah is an interesting discussion to be used as an analysis approach of economic democracy study. This article is an research with the library method that reveals about economic democracy and Maqa??id shari?ah with conten analysis. The conclution of this study is economic democracy has fullfill the aim of Maqa??id shari?ah in the maintenance of religion (?if? al-di?n), maintenance of life (?if? al-nafs), the maintenance of reasonable (hif? al-aql), maintenance of ancestry (?if? al-nasl) and maintenance of treasure (?if? al-ma?l). In addition to these five aims, there is additional aim of economic democracy system, namely maintenance of state (?if? al-wa?on) as the liberation of the country from colonial efforts as colonial economic system at that time.